Installation Des Colons Agricoles Dans Le Terroir Du Confluent Ouème-Beffa À Ouèsse Au Centre Du Bénin: Impacts Socio-Economique Et Environnemental - Alomasso, Alphonse A.; Bosco, Vodounou Jean; Adigbegnon, Marcel (European Scientific Journal, ESJ, 2018)
The depletion of natural resources has resulted in a change in farming systems and the change in social relations that have long characterized African societies. For example, slash-and-burn agriculture that has characterized cropping systems in these countries has shown its limits in some areas. In Benin it took new forms resulting in the abandonment of certain soils for the benefit of others: the migration of peasants. This phenomenon has become so widespread today that pressure has been felt in previously vacant areas, leading to many conflicts and tensions between indigenous and immigrants, creating a degree of land insecurity for indigenous people that does not allow them to do so. to adopt sustainable practices for a good use of the land resource. The results obtained were possible thanks to the fieldwork and through the deductive method and descriptive, analytical and cartographic approach. This study has identified the socio-economic and environmental impacts of the massive arrival of agricultural settlers in the land of the confluence Oumé-Beffa, and identify the constraints related to the colonization of agricultural land by migrants and the strategies that they develop to better valorise their contracts in order to propose adapted systems for a sustainable management of the fertility of the lands in the conflict of Oueme-beffa in Ouessè.